The influence of sources of information in voting decision making: a case study of Cybercity Apartment Residents, Kota Kinabalu Sabah/ Siti Fatimah Mapelendo ... [et al.] - Mapelendo, Siti Fatimah; Jonytim, Sakurah; Zaaba, Zuraidah; Gunggut, Haijon (Universiti Teknologi MARA, Sabah, 2024)
This study aims to examine the influence of sources of information on voting decision-making among the residents of Cybercity apartments in Kota Kinabalu. In today’s digital age, individuals have access to a plethora of information sources that can potentially shape their perceptions and decision-making processes, particularly in the context of voting decisions. This research seeks to identify the various sources of information on social media (economic performance, political experts, policy experts, community, and religious beliefs) that residents rely on when making decisions about voting decision making. Through surveys and data analysis, this study uncovered the specific roles that different sources of information play in the voting decisions of Cybercity apartment residents. Additionally, this research explores the extent to which residents trust and prioritise certain sources of information on social media and how this ultimately influences their vote. By gaining a better understanding of the impact of sources of information on social media on voting decisions within this unique residential community, this study contributes valuable insights into voter decision-making dynamics in contemporary Society.